2020
DOI: 10.1038/s41598-020-76337-2
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy reveals age- and sex-related differences in cortical bone from people with osteoarthritis

Abstract: Bone strength in human cortical bone is determined by the composition and structure of both the mineral and collagen matrices and influenced by factors such as age, gender, health, lifestyle and genetic factors. Age-related changes in the bone matrix are known to result in loss of mechanical strength and increased fragility. In this study we show how Raman spectroscopy, with its exquisite sensitivity to the molecular structure of bone, reveals new insights into age- and sex-related differences. Raman analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…3 A), these ionic exchanges should be attributed to an evolution of the pre-existing apatitic phase. The maturation of nanoapatites in solution involves both an increase in crystallinity and the evolution of the elemental composition toward stoichiometric hydroxyapatite [ 20 , 88 , 89 ]. A progressive increase in crystallinity of the fine CDHA with incubation time was corroborated using XRD, with the observation of more intense and better resolved peaks with incubation time ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3 A), these ionic exchanges should be attributed to an evolution of the pre-existing apatitic phase. The maturation of nanoapatites in solution involves both an increase in crystallinity and the evolution of the elemental composition toward stoichiometric hydroxyapatite [ 20 , 88 , 89 ]. A progressive increase in crystallinity of the fine CDHA with incubation time was corroborated using XRD, with the observation of more intense and better resolved peaks with incubation time ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…proline (858 cm -1 ) and C-C stretching; protein backbone (816 cm -1 ) (Nieuwoudt et al 2020, Mansfield and Winlove 2017, Kumar et al 2015, Pezzotti et al 2022, Martinez et al 2019, Khalid et al 2018, Gao et al 2021, Takahashi et al 2014, Casal-Beiroa et al 2021, Prokopi et al 2021, Cárcamo et al 2012, Asaoka et al 2022.…”
Section: Introductionmentioning
confidence: 99%
“…Phytoplankton cells have a highly multicomponent biomolecular composition. To address this issue, statistical multivariate analysis methods, which have been successfully applied in other complex systems, have been proposed. To date, however, literature on the application of chemometric methods for phytoplankton Raman analysis is limited to reports on nutrient composition or depletion, the detection of invasive problematic phytoplankton species, and one report on cell viability. ,, These studies showed the great potential of Raman spectroscopy but suffered from the limitations mentioned above and the reported limited application of chemometric methods, which hindered the identification of broader trends in the complex Raman spectra of phytoplankton.…”
Section: Introductionmentioning
confidence: 99%